Lareh Nan Bunta: Power Systems and The Concept of Musical Aesthetics in Talempong Basaua in Luhak 50 Koto Minangkabau (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2018)
The goal of this article is to bring to light lareh nan bunta as a form of representation of the system of democracy – or power – developed by Dt. Nan Sakelap Dunia. The discussion in this paper uses a qualitative method which is backed up by quantitative data. The data was collected through participant observation, interviewing, discussion, and analysis. The analysis was carried out using a descriptive method using theoretical reasoning, with knowledge of aesthetics and art. The results of the research show that conceptually, talempong basaua is a musical reality which represents lareh nan bunta in Luhak 50 Koto Minangkabau. Lareh nan bunta is a synthesis of the influence of power – or dialectic – between lareh kotopiliang (autocracy) and lareh bodicaniago (democracy), each with its own system of leadership. The dualism in the autocratic and democratic systems of power form a balancing power known as lareh nan bunta – a combination of all three existing conceptions. Lareh nan bunta is also reflected in the concept of musical aesthetics in talempong basaua in Luhak 50 Koto Minangkabau. Talempong basaua represents a combination of two musical concepts, namely talempong and the rhythms or irama of dendang (vocal music), which are combined to create a new genre.